Blockchain and distributed ledger technologies for supply chain traceability: industry considerations and consumer preferences - Dionysis, Symeon (2023)
Several businesses and academic circles were quick to proclaim blockchain, the distributed ledger technology behind digital currencies, as the solution to a plethora of industry challenges. That was especially true for supply chain management and traceability applications for coffee products, where the technology's features were viewed as a potential solution to longstanding issues of communication inefficiencies, production monitoring, and communicating provenance information to the end consumer. However, despite the excessive amount of investment, research, and experimentation, blockchain growth and adoption have stagnated. This thesis suggests that a plausible reason for the current gridlock the technology finds itself in lies in the absence of primary research that goes beyond its technical implementations and provides clear insights on both how industry professionals understand blockchain and structure their decision-making process to adopt it, as well as on how consumers perceive coffee products that utilise the technology for traceability and provenance purposes.